Dwelling adaptation in a particular resident through patron-client relationship - Latupeirissa, Hendrico Firzandy; Sihombing, Antony; Fuad, Achmad Hery (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
This research is conducted to determine the underlying reasons a particular theater group adjusts to a certain setting and conditions in order to maintain its continued presence in a location. One of the reasons previously identified for the acceptance and adaptation is the low affordability of housing. Therefore, qualitative design and grounded theory method were applied, and the habitation form of the group was observed to determine their dwelling adaptation. The results showed that the role of the government as patron was very important for the survival of groups, specifically in providing increasingly affordable housing for urban poor and catering for psychological and social welfare. Client was also discovered to have become increasingly attached to the housing assistance and considered patron as important figures and protectors. It was argued that certain stakeholders have an important role in producing residential designs to empower and maintain the survival of urban poor.